The food environment in favelas is associated with the presence of arterial hypertension and diabetes in socially vulnerable women - Luiz Gonzaga Ribeiro Silva-Neto; Risia Cristina Egito de Menezes; Juliana Souza Oliveira; Nathalia Paula de Souza; Thays Lane Ferreira dos Santos; Telma Maria de Menezes Toledo Florêncio (Public Health Nutrition)
Abstract